A Polynomial Splines Identification Method Based on Control Nets. (19th August 2020) - Wang, Zhihua; Kang, Hongmei
Abstract : In this study, based on Polynomial Splines with control nets, an identification method is investigated. We introduce polynomial splines with control nets defined over T-mesh. The basic idea is to extend T-vertices such that those T-vertices become interior cross vertices or boundary vertices. To this end, we introduce the design-suitable T-mesh for constructing polynomial splines with control net. In design-suitable T-meshes, there are no extra basis vertices produced by an appropriate extension of T-vertices. The basis functions are defined over each vertex in a design-suitable T-mesh by the means of constructing PHT-splines basis functions.